Proteomic biomarkers for survival in systemic sclerosis-associated pulmonary hypertension - Valentine Mismetti; Xavier Delavenne; David Montani; Souad Bezzeghoud; Olivier Delezay; Sophie Hodin; David Launay; Sylvain Marchand-Adam; Hilario Nunes; Edouard Ollier; Martine Reynaud-Gaubert; Jean Pastre; et al. (Respiratory Research, 2023)
Abstract Background Interstitial lung disease (ILD) and pulmonary hypertension (PH) represent the major causes of mortality in systemic sclerosis (SSc). Patients with systemic sclerosis and combined PH and ILD (SSc-PH-ILD) generally have a poor prognosis. Predictors of survival and of potential benefit of treatment are lacking in patients with SSc-PH-ILD. Objective To identify specific plasma protein expression patterns associated with survival in patients with SSc-PH-ILD. Materials and methods Post-hoc analysis of a prospective multicenter French study in patients with PH-ILD. An untargeted proteomic analysis using mass spectrometry was performed to identify plasma protein changes associated with long-term overall survival in patients with SSc-PH-ILD. Results Thirty two patients were included in the analysis, of whom 13 died during follow-up (median survival: 76.5 months). At baseline, survivors had less severe hemodynamic impairment [pulmonary vascular resistance of 4.4 Wood Units (IQR 3–5.2) vs. 6.2 Wood Units (IQR 4.2–10.7)] and higher carbon monoxide diffusing capacity [median 39% (IQR 35–44%) vs. 25% (IQR 22–30.5%)], than the 13 patients who died. Seven proteins, associated with haemostasis and fibrosis, were differentially expressed according to patients’ survival. In the survivor group, two proteins were increased (ADAMTS13, SERPIND1) and five were decreased (PTGDS, OLFM1, C7, IGFBP7, FBN1) compared to the non-survivor groups. Conclusion The prognosis of SSc-PH-ILD patients is poor. This proteomic approach found 7 plasma proteins (involved in haemostasis and fibrosis pathways) associated with survival. These potential biomarkers may be good candidates to prognostic enrichment.